2014
DOI: 10.1177/1440783314536792
|View full text |Cite
|
Sign up to set email alerts
|

Gains and losses: African Australian women and higher education

Abstract: This article argues that African women migrants in Australia are increasingly enrolling in and successfully completing tertiary study, usually at high emotional and financial cost. While this qualitative study has shown that both refugee-background and non-refugee African Australian women's enrolment in higher education is enabling new forms of participation and belonging in resettlement, it continues to challenge the women's more traditional cultural roles and identities. This article argues that these gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 29 publications
2
25
0
1
Order By: Relevance
“…The findings of this study indicate that University of Sanctuary scholars found that living in direct provision had a negative impact on them personally and on their studies, in particular the lack of quiet study space and poor Internet access. These findings are generally compatible with previous research, which identified the logistical and digital barriers that refugee students face while studying (Harris, Spark, and Ngum Chi 2015;O'Reilly 2018). The data revealed the difficulties experienced by refugees accessing HE in Ireland.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings of this study indicate that University of Sanctuary scholars found that living in direct provision had a negative impact on them personally and on their studies, in particular the lack of quiet study space and poor Internet access. These findings are generally compatible with previous research, which identified the logistical and digital barriers that refugee students face while studying (Harris, Spark, and Ngum Chi 2015;O'Reilly 2018). The data revealed the difficulties experienced by refugees accessing HE in Ireland.…”
Section: Discussionsupporting
confidence: 90%
“…For others, the pressure to be successful could be overwhelming (Earnest et al 2010b). Besides the practical implications of finding it hard to have a place to study, refugee can feel alienated from their friends and families while studying (Harris, Spark, and Ngum Chi 2015).…”
Section: (Page Number Not For Citation Purpose)mentioning
confidence: 99%
“…Long-standing research underscores the importance of post-migration experiences for the well-being of resettling refugees. For example, adjustment to the new socio-cultural context (Berry, Kim, Minde, & Mok, 1987; Wille, 2011) and changing family dynamics and gender roles (Deng & Marlowe, 2013; Harris, Spark, & Watts, 2015; Marlowe, 2012) as well as host-country reception (Losoncz, 2011; Nwadiora & McAdoo, 1996) have been shown to be relevant. Resettlement stressors include unemployment and underemployment (Murray & Skull, 2005), housing problems and residential mobility (Harte, Childs, & Hasting, 2009), inadequate social support networks (Schweitzer, Greenslade, & Kagee, 2007), concerns about family abroad and obligations to send remittances (Baak, 2014; Savic, Chur-Hansen, Mahmood, & Moore, 2013; Schweitzer et al, 2006) and difficulties in accessing health services (Lamb & Smith, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Así, diferentes estudios atienden al análisis de los migrantes refugiados, en conjunción con otras variables como el género (Watkins et al, 2012;Harris et al, 2015), o en comparación con otras situaciones legales como la condición de indocumentados y residentes regularizados (Murray y Marx, 2013).…”
Section: Papers (Revista Deunclassified
“…Therefore, distinct studies consider the analysis of migrant refugees, in connection with other variables such as gender (Watkins, 2012;Harris, 2015), or in comparison with other legal situations such as the 12 Based on the survey data and that of the focus groups, the extension of diverse forms of discrimination perceived amongst the consulted population is detected. condition of being undocumented and regularized residents (Murray & Marx, 2013 From a legal perspective (but in the intermediate area of social-legal studies and applied social-legal action research), Makkonen (2002) mentions the importance of qualitative information when considering multiple discrimination.…”
Section: La Revista Española De Investigacionesmentioning
confidence: 99%